Efficiency of cooperative business units through the application of engineering in the KAGUM cooperative, Malacca - Suryani, Suryani; Rinda Lestari; Tomi Tamara; Karfindo (Journal of Community Service and Application of Science, 2025)
The KAGUM cooperative is a cooperative in Malaysia, namely in Malacca, which has a lot of members, around 700 teachers. Where the activity with technical engineering is somewhat lacking. In addition, this cooperative has an inn rental business, which is a multi-storey building in front of the office. The application of engineering in the management of cooperative business units is sought on the community service of lecturers from Indonesia in various fields and is an important strategy in improving operational efficiency and competitiveness of cooperatives in the modern era. The application of this community service carried out technical engineering carried out at the KAGUM Cooperative, Malacca, as a cooperative model based on productivity and work efficiency. The methods used include field observations, semi-structured interviews, and documentation of the work system and operations of the cooperative business unit. The community service from Indonesia at the KAGUM Cooperative shows that the optimization of workflows, the application of appropriate technology, and technical training for members and administrators of the cooperative contribute significantly to the cost efficiency and increase of the income of this cooperative. The application of engineering not only has an impact on the productivity of business units, but also strengthens the cooperative governance system as a whole.